(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Jalaluddin Rumi’s philosophical views on humanity are highly relevant today in enhancing the worldview of the younger generation and supporting their spiritual development. The rapid advancement of modern technologies, globalization processes, and swift changes in society can lead to the decline of moral, ethical, and spiritual values among young people. This article analyzes Jalaluddin Rumi’s views on humanity from a philosophical perspective.